Assessment Of Teachers’ Personality Traits As A Predictor Of Students’ Academic Performance In Chemistry In Senior Secondary Schools In Osun State - Olajide, S.Olayinka; Adebayo, Aderonke A. (Advances in Social Sciences Research Journal, 2019)
The study assessed teachers’ personality traits as a predictor of students’ academic performance in Chemistry in senior secondary schools in Osun State. It investigated and analysed relationship between teachers’ personality traits such as attitude, qualification, and knowledge of subject matter etc. on students’ academic performance in Chemistry in senior secondary schools in Osun State. These were with a view to providing information on students’ academic performance in the subject in the study area. The study adopted the descriptive survey research design. The population for the study comprised all Chemistry students and their teachers in senior secondary schools in Osun State. Three hundred senior secondary two (SSII) students were randomly selected from thirty randomly selected senior secondary schools in Osun State using simple random sampling technique. All the Chemistry teachers in the all the selected schools were purposively used for the study. The three instruments used for data collection are; Teachers’ Personality Traits Questionnaire (TPQ), Students’ Perception of Teachers’ Personality Traits Questionnaire (SPTPTQ) and Students’ Results in Chemistry in their previous terms. The results of the study showed that there is significant relationship between teachers’ attitude and students’ academic performance in Chemistry (r=0.087; p<0.05). The results of the study also revealed that there is significant relationship between teachers’ qualification and students’ academic performance in Chemistry (F=0.025; p<0.05). The results of the study further showed that there is significant relationship between teachers’ knowledge of subject matter and students’ academic performance in Chemistry (r=0.210; p<0.05). Moreover, the results of the study revealed that there is significant relationship between teachers’ self-efficacy and students’ academic performance in Chemistry (r=0.125; p<0.05), and finally the results of the study showed that there is significant relationship between teachers’ years of experience and students’ academic performance in Chemistry (F=0.100; p<0.05). The study concluded that teachers’ personality traits predict students’ academic performance in Chemistry in senior secondary schools.